Thymoquinone Prevents β-Amyloid Neurotoxicity in Primary Cultured Cerebellar Granule Neurons - Siti Aisyah Abd Ghafar; Norsharina Ismail; Maznah Ismail; Musalmah Mazlan; Latiffah Abdul Latiff; Mustapha Umar Imam; Shahid Iqbal; Nur Hanisah Azmi; Kim Wei Chan (Springer, 2024)
Non-Indexed Publication